Toward Generating Subtype-Specific Mesencephalic Dopaminergic Neurons in vitro - Cardoso, Tiago; Lévesque, Martin (Frontiers in Cell and Developmental Biology, 2020)
Mesencephalic dopaminergic (mDA) neurons derived from pluripotent stem cells (PSCs) have proven to be pivotal for disease modelling studies and as a source of transplantable tissue for regenerative therapies in Parkinson’s disease (PD). Current differentiation protocols can generate standardized and reproducible cell products of dopaminergic neurons that elicit the characteristic transcriptional profile of the ventral midbrain. Nonetheless, dopamine neurons residing in the mesencephalon comprise distinct groups of cells within diffusely defined anatomical boundaries and with distinct functional, electrophysiological and molecular properties. Here we review recent single-cell sequencing studies that are shedding light on the neuronal heterogeneity within the mesencephalon and discuss how resolving the complex molecular profile of distinct sub-populations within this region could help refine patterning and quality control assessment of PSC-derived mDA neurons to subtype-specificity in vitro. In turn, such advances would have an important impact in improving cell replacement therapy, disease mechanistic studies and drug screening in PD.